Efficacy of pharmacotherapy against core traits of borderline personality disorder: meta-analysis of randomized controlled trials. - Nosè, M; Cipriani, A; Biancosino, B; Grassi, L; Barbui, C (2006)
We conducted a meta-analysis of published randomized, placebo-controlled clinical trials that evaluated the effect of pharmacotherapy in patients with borderline personality disorder. Comprehensive searches of the MEDLINE, EMBASE, PsychLIT and Cochrane Central Register of Controlled Trials databases were performed using web-based search engines. Twenty articles, reporting 22 placebo-controlled comparisons, were included in the meta-analysis: eight involved antipsychotics, seven antidepressants and seven mood stabilizers. Antidepressants (four studies, standardized mean difference -0.55, 95% confidence interval -0.92, -0.17) and mood stabilizers (six studies, standardized mean difference -1.74, 95% confidence interval -2.76, -0.73) were effective against affective instability and anger, but did not produce significant benefits against impulsivity and aggression, unstable relationships, suicidality and global functioning. Antipsychotics as a class had a positive effect in terms of impulsivity and aggression (three studies, standardized mean difference -0.31, 95% confidence interval -0.63, -0.003), interpersonal relationships (three studies, standardized mean difference -0.52, 95% confidence interval -0.87, -0.17) and global functioning (seven studies, standardized mean difference -0.56, 95% confidence interval -1.00, -0.11). No difference was observed between pharmacotherapy and placebo in terms of participants leaving the study early. Pharmacotherapy can exert a modest beneficial effect on some core traits of borderline personality disorder.